Gambaran Tingkat Pengetahuan Dan Sikap Akseptor KbDalam Penggunaan Alat Kontrasepsi Suntik Di DesaKateguhan Kabupaten Boyolali - Krystiyanto, Randy; , Arina Maliya S.Kep.,M.Si.Med; , Vinami Yulian, S.Kep., Ns (2016)
One of contraception kinds preferred most by the Indonesian citizens is contraceptive injection. The reasons of its use are because it is safe, its very effective performance, its cheap price, is able to be used by all females in the reproduction age, the return of fertility is slower, and is appropriate to the lactation period because it does not reduce the production of mother's milk. The influencing factors in the use of contraceptive injection are: factors of predisposition (age, education, knowledge, amount of children), factors of possibility (the availability of contraception tools) and the supporting factors (the husband's support, the health officers' support). This research aimed at knowing the descriptions on the knowledge level and the family planning acceptors' attitude in the use of contraceptive injection in Kateguhan Village, Boyolali Regency. This research was a descriptive research. Sample of the research was 74 active family planning acceptors in Kateguhan Village through the technique of proportional random sampling. The data collection used questionnairanalyzed using the test of descriptive univariat. The conclusions of the research showed that most of the respondents were 20 - 30 years old, having an educational background of senior high school, having 2 children, as a housewife, and usingthe 3-month contraceptive injection. The knowledge level of the fertile couplemothers of the contraceptive injection users in Kateguhan Village, Boyolali Regency was mostly enough which was influenced by the factors of the Puskesmas officers' service and the respondents' educational level. The description on the attitude of the fertile couplemothers of the contraceptive injection users in Kateguhan Village, Boyolali Regency was mostly positive which was influenced by the factors of the the contraception use experience and the respondents' age.